Video Visualization of a String Quartet Performance of a Bach Fugue: Design and Subjective Evaluation - Olivier Lartillot; Dana Swarbrick; Finn Upham; Carlos Eduardo Cancino-Chacón (Music & Science, 2025)
Visualizing music—through music notation, analytical representations, or music videos—might potentially boost the appreciation of music in all its richness. The purpose of this study was to design and test a visualization strategy aimed at explicating to a large audience with diverse backgrounds—especially novices—the multifaceted beauty of the final Contrapunctus in J.S. Bach's The Art of Fugue , performed by the Danish String Quartet. At the surface level of the musical structure, the rich fluctuation of pitch shaped by each musician was depicted in the form of undulating pitch curves. At a deeper structural level, the repetition of pitch curves, distinctive of fugues, was highlighted through vertical alignment—inspired by a technique called paradigmatic analysis, originating from anthropology and music semiology. The visualization was initially prototyped in the form of a real-time technology as part of the MusicLab Copenhagen research concert. The concert audience focused on the performance itself, and did not pay much attention to, nor appreciate, the visualization. To evaluate more thoroughly the potential of the visualization, participants with varied musical expertise and taste were invited to listen to a recorded performance of the piece and watch the visualization on their own computer. A large majority reported that they felt they understood the visualization, around half of them felt that it enhanced their musical understanding, and a small group felt that it helped them to better appreciate the music.